STRATEGI PENINGKATAN PENERIMAAN PENDAPATAN PAJAK REKLAME DIKABUPATEN BOGOR - Sulviane, Indah Ayu; Harianto, Harianto; Hakim, Dedi Budiman (Jurnal Manajemen Pembangunan Daerah, 2014)
Implementation for fiscal decentralitation, local government that required excavation and development of the area and potential revenue sources to increase regional revenue.The objective of this research is to analyze the factors that influence the potential of advertisement tax revenue, reviewing management organization of advertisement tax is implemented, analyzed the taxpayer perceptions of the advertisement tax and revenue enhancement strategy billboard tax in Bogor regency.The data used are secondary and primary data was analyzed by descriptive quantitative and qualitative. The analytical method used is a regression method, the calculation of Efficiency and Effectiveness taxes. As for the design of this research program using Analysis IFE, EFE and IE, SWOT Analysis and Analysis QSPM.Results of the discussion, in the realization of the tax revenue target advertisements Bogor regency government always exceed the achievement of the targets, with the exception of 2006, when the realization is not achieved then the effective rate also decreased and the percentage of tax efficiency at the Bogor Regency advertisement in 2000 - 2012 looks good and the smaller the ratio efficiency means that the performance of the Bogor regency government for the better collection of advertisement tax.Based on the partial test table, budget, number of employees, regulatory and tax payers have a significant impact on tax revenue billboard on the real level of 10%. Constraints faced in collecting data on the potential of the advertisement tax is the lack of accurate data due to the limited ability of local government officials, the need for legal certainty in the billboard tax management.The draft strategy are as follows 1) conduct outreach and education on an ongoing basis to increase public awareness, 2) build a system of valid and accurate data; 3) give reward and punishment.Keywords: Strategy, Regional Revenue, Advertising Tax ABSTRAK Wujud otonomi dan desentralisasi fiscal, pemerintah daerah berusaha melakukan penggalian dan pengembangan sumber pendapatan potensial untuk meningkatkan pendapatan asli daerah.Tujuan penelitian menganalisis faktor-faktor yang mempengaruhi penerimaan pajak reklame, mengkaji manajemen penyelengaraan pajak reklame, menganalisis persepsi masyarakat terhadap pajak reklame dan menyusun strategi peningkatan pendapatan pajak reklame di Kabupaten Bogor.Data yang digunakan data sekunder dan primer, dianalisis secara deskriftif kuantitatif, kualitatif. Metode analisis yang digunakan Regresi, Efisiensi dan Efektivitas pajak. Perancangan program menggunakan Analisis IFE, EFE dan IE, Analisis SWOT dan Analisis QSPM.Hasil pembahasan, dalam merealisasikan target pendapatan pajak reklame selalu melebihi target yang ditetapkan, dengan pengecualian tahun 2006, ketika realisasi tidak tercapai maka efektivitas mengalami penurunan dan persentase efisiensi pajak reklame di Kabupaten Bogor tahun 2000-2012 terlihat baik dan semakin kecil rasio efisiensi mengandung arti kinerja pemerintah Kabupaten Bogor untuk pemungutan pajak reklame semakin baik.Berdasarkan tabel uji parsial, anggaran, pegawai, peraturan dan wajib pajak memiliki pengaruh yang signifikan terhadap penerimaan pajak reklame pada taraf nyata 10%. Kendala yang dihadapi yaitu kurangnya data yang akurat, keterbatasan kemampuan aparat, masih kurang nya kesadaran masyarakat dan perlunya ada kepastian hukum. Rancangan strategi adalah 1) melakukan sosialisasi penyuluhan secara berkesinambungan 2) membangun sistem data yang valid dan akurat 3) memberikan reward dan punishment sesuai ketentuan.Kata Kunci : Strategi, Pendapatan Asli Daerah, Pajak Reklame